Regional cooperation and integration : intergovernmentalism approach to regional integration: a case of the African Continental Free Trade Area and effects on trade - Chipp, Kerry (University of Pretoria, 2021)
Mini Dissertation (MPhil)--University of Pretoria, 2020.